Effects of different drying methods on the physicochemical properties and antioxidant activities of isolated acorn polysaccharides. (February 2019) - Ahmadi, Shokouh; Sheikh-Zeinoddin, Mahmoud; Soleimanian-Zad, Sabihe; Alihosseini, Farzaneh; Yadav, Hariom
Abstract: Our earlier studies showed that the Acorn Polysaccharides (AP), as a forest byproduct, have a good prebiotic properties and antioxidant activity, hence can be used as an ingredient to produce functional foods. Three drying methods (freeze, hot air and vacuum drying) in different temperatures were comparatively studied on the physicochemical properties (solubility, water and oil-holding capacity [OHC/WHC]), bioactivity (resistance to acidic and enzymatic digestions, effect on a probiotic strain growth) and antioxidant activity of AP along with the structural changes. Results suggest that the drying methods in combinations of temperatures and time of drying process affect physicochemical properties, antioxidant activity and bioactivities of AP. Freeze dried AP exhibited the highest solubility, WHC, OHC and antioxidant activity, digestibility with simulated gastrointestinal juices and fermentable by a Lactobacillus plantarum . Whereas, hot air dried (80 °C) exhibited second highest antioxidant and functional activities like solubility, WHC, OHC and fermentation. FTIR analysis showed that the changes caused by varying drying methods of AP starch are related to its amorphous or crystallinity structure and differences in functional group. Overall, these results suggest that freeze drying and hot air drying at 80 °C can be appropriately use to obtain a functional polysaccharide from acorn, as a prebiotic (resistant starch). Highlights: Drying method and condition significantly affect properties of acorn polysaccharide. AP most probably is a kind of resistant starch (prebiotic) revealed by FTIR. Drying method changed functional groups (OH) and amorphous structure of AP. Freeze-dried AP sample showed the best bioactivity and functional properties. Air drying in suitable temperature (80 °C is suggested) is also appropriate for obtaining bioactive AP.